Review of the Evidence on Preventing and Managing Acute Kidney Injury after Cardiac Surgery with Amino Acids - Ali Jabbari; Behrang Nooralishahi; Alireza Jahangiri fard (Archives of Anesthesia and Critical Care)
Background: Acute kidney injury (AKI) after cardiac surgery leads to serious outcomes, including higher mortality and increased risk of chronic kidney disease. The pathophysiology includes hemodynamic changes, inflammation, and direct renal damage. Key risk factors are chronic kidney disease, older age, diabetes, hypertension, and surgical issues like cardiopulmonary bypass (CPB) and nephrotoxic agents. CPB can cause inflammation, worsening renal blood flow and glomerular filtration rate (GFR). Preventing AKI requires a comprehensive approach that encompasses preoperative optimization, intraoperative management, and postoperative care. Important strategies include optimizing the CPB circuit, using blood cardioplegia for better myocardial and renal protection, and managing fluid balance. This study aimed to examine the factors leading to acute kidney injury during heart surgery and to identify strategies for addressing it. Methods: Research articles from information sources and databases over the past five years were analyzed using keywords. The studies were classified and summarized according to the disease's pathophysiology and management strategies and clinically evaluated. The findings were assessed based on clinical evidence and compiled into a review article. Results: Amino acids are essential for renal protection, as they enhance blood flow, improve GFR, scavenge reactive oxygen species (ROS), modulate inflammation, support cellular energy, inhibit apoptosis, aid in protein synthesis, and maintain renal autoregulation. Specific amino acids, including L-Arginine, L-Citrulline, L-Carnitine, Taurine, L-Glutamine, L-Cysteine, L-Methionine, L-Ornithine, L-Tyrosine, and Branched-Chain Amino Acids (BCAAs), have demonstrated protective effects. These amino acids can enhance postoperative GFR and potentially lower the risk of AKI by bolstering renal functional reserve and stimulating local renal growth factors. Conclusion: A comprehensive strategy incorporating preoperative, intraoperative, and postoperative measures, along with the judicious use of amino acids, is essential for preventing AKI and improving outcomes in patients undergoing cardiac surgery.